2003
DOI: 10.1016/s0277-3791(02)00249-4
|View full text |Cite
|
Sign up to set email alerts
|

Age of the Mono Lake excursion and associated tephra

Abstract: The Mono Lake excursion (MLE) is an important time marker that has been found in lake and marine sediments across much of the Northern Hemisphere. Dating of this event at its type locality, the Mono Basin of California, has yielded controversial results with the most recent effort concluding that the MLE may actually be the Laschamp excursion (Earth Planet. Sci. Lett. 197 (2002) 151). We show that a volcanic tephra (Ash x15) that occurs near the midpoint of the MLE has a date (not corrected for reservoir eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
6
60
0
Order By: Relevance
“…Evidence of the Younger Dryas cold event is not observed in the rock magnetic signature between 10 and 15 ka, where the k ARM record shows a gradual increase contrasting to the Greenland ice core isotope record. As mentioned before, the Mono Lake excursion was suggested to correspond to a paleointensity low at about 32 ka (Benson et al, 2003). It was also reported that a peak of 36 Cl concentration occurs between the D-O events 6 and 7 at about 32 ka in the GRIP ice core (Wagner et al, 2000).…”
Section: Environmental Magnetic Recordmentioning
confidence: 66%
See 1 more Smart Citation
“…Evidence of the Younger Dryas cold event is not observed in the rock magnetic signature between 10 and 15 ka, where the k ARM record shows a gradual increase contrasting to the Greenland ice core isotope record. As mentioned before, the Mono Lake excursion was suggested to correspond to a paleointensity low at about 32 ka (Benson et al, 2003). It was also reported that a peak of 36 Cl concentration occurs between the D-O events 6 and 7 at about 32 ka in the GRIP ice core (Wagner et al, 2000).…”
Section: Environmental Magnetic Recordmentioning
confidence: 66%
“…Kent et al (2002) and Zimmerman et al (2006) suggested that the anomalous paleomagnetic feature at Mono Lake is correlative with the Laschamp excursion at about 41 cal kyr BP. On the other hand, Benson et al (2003) showed that the excursion is dated at about 32 cal kyr BP and correlated with a paleointensity low in the NAPIS-75 record . It is therefore important to delineate the geomagnetic field variation corresponding to the excursion around 32 ka in widely distributed locations.…”
Section: Inclination (°)mentioning
confidence: 98%
“…If the latter is the case, the ND, SU, and WU groups occurred at about 29, 50 and 55 ka, respectively, although the interval between the ages of the SU and WU groups (approx. 5000 years) is not much more than estimated durations for geomagnetic excursions (1500-2000 years; Benson et al, 2003;Laj et al, 2006).…”
Section: The Ages Of the Auckland Excursionsmentioning
confidence: 84%
“…Two well-established excursions in this interval are the Laschamp excursion reported from the lava flows in France (Bonhommet and Zäringer, 1969), dated at 40.4±2.0 ka (2σ ) (Guillou et al, 2004), and the Mono Lake excursion identified from lake sediments in western North America (Denham and Cox, 1971), dated at approximately 30 ka (Benson et al, 2003). These two distinct excursions are considered to have occurred at 30 and 40 ka, respectively, although a few researchers have noted that the Mono Lake excursion at the original locality may be a record of the Laschamp excursion (Kent et al, 2002;Zimmerman et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Both these well-documented excursions are generally agreed to have inclination anomalies with durations of about 1,500 years [e.g., Laj et al, 2000;Teanby et al, 2002;Benson et al, 2003]. Given the similarity of paleodirections for the five Auckland volcanoes and the rarity and short duration of excursions, it seems highly unlikely that more than one excursion event has been recorded.…”
Section: Discussionmentioning
confidence: 99%